The Institutional Renewal in Settlement of Disputes of Local Election Results - Heru Widodo (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2018)
Abstract. Since the first step of local election in 2015, the authority of adjudicating a dispute of local election’s result has been run by The Constitutional Court (MK) until a special judicial board before the national election held. An ideal design of the institutional renewal to adjudicate a controversy of local election’s result, could be a part of judicial environment under The Supreme Court (MA) supervision, or may becomes a new institution or replaces another institution by attaching to the authorized institution, named: Bawaslu, PT TUN or MK. Bawaslu was become the one of the institution which fulfills the requirements. Started from a legislative election on 2014, Bawaslu has an authority of resolving a dispute among the candidates of general election or between the candidates and the committee. And since the national election in the year 2017, Bawaslu has given the authorization to settle up an administrative violation, a conflict of local election and to handle a money politics through TSM. The authority of the dispute court of election results is proposed not only on the controversy over the calculation result, but also including unreachable legal phenomenon with law enforcement on criminal system and stage of election dispute, as an inseparable part.Keywords: institutional renewal, dispute result, national election.Abstrak. Sejak pemilihan serentak tahap pertama tahun 2015, wewenang mengadili sengketa hasil pemilukada dijalankan Mahkamah Konstitusi sampai dibentuk badan peradilan khusus sebelum pelaksanaan pemilihan serentak nasional. Disain pembaharuan kelembagaan yang ideal untuk mengadili sengketa hasil pemilukada serentak, dapat menjadi bagian dari lingkungan peradilan dibawah Mahkamah Agung, dapat pula menjadi lembaga baru ataupun mereposisi lembaga dengan cara melekatkan pada lembaga yang saat ini berwenang menyelesaikan sengketa pemilihan, yakni : Bawaslu, PT TUN atau MK. Bawaslu menjadi salah satu pilihan lembaga yang memenuhi persyaratan. Sejak Pemilu Legislatif 2014, Bawaslu berwenang menyelesaikan sengketa antarpeserta pemilu maupun antara peserta dengan penyelenggara, dan sejak Pemilukada Serentak 2017, bahkan diberi wewenang memutuskan pelanggaran administrasi, sengketa pemilukada sampai penanganan politik uang (money politics) secara TSM. Kewenangan peradilan sengketa hasil pemilihan diusulkan tidak hanya atas perselisihan atas hasil perhitungan, tetapi memasukkan peristiwa hukum yang tidak terjangkau dengan penegakan hukum dalam sistem pidana dan tahap sengketa pemilihan, sebagai bagian yang tidak terpisahkan. Kata kunci : pembaharuan kelembagaan, sengketa hasil, pemilukada serentak